From pattern to place: The architecture of a living fish market in Gothenburg - Kotama, Diana (My University, 2025)
In today’s urbanized and digitized world, knowledge of where food comes from is increasingly scarce and access to fresh, locally sourced food becomes rare. Supermarket culture,convenience-driven lifestyles and industrial food systems weaken our relationship with food origins, turning nourishment into a transaction rather than an experience. This disconnection threatens not only public health and sustainability but also cultural identity. In Gothenburg, a city historically tied to the sea, traditional fish markets lose much of their civic and cultural significance. This thesis explores how architecture restores these connections by reimagining the fish market as a spatial and social regeneration tool. Drawing from Christopher Alexander’s A Pattern Language and the theory of living structures, the project adopts a narrative, site-specific design methodology. It develops a framework through modular exploration, pattern testing and site analysis in Fiskhamnen. The design mirrors the rhythms of local marketplace interactions and provides transparency in food production through living spaces that offer education and experience. Two research questions guide the project: How can architectural design and food spaces such as a fish market reconnect social interactions among food producers and consumers in one place? How can pattern-based design methods shape a contemporary fish market that is suited to Fishmarket in Fiskhamnen , Gothenburg? The resulting design is more than a market. It becomes a spatial narrative. Traditionally, processes such as gutting, sorting and storage are hidden from public view. This project makes them partially visible through architectural elements like the Salt Trace, ice storage and Gut Room. These spaces serve as infrastructure and educational tools, transforming the market from a purely commercial typology into a civic space that dissolves boundaries between front and back, clean and messy, public and private. By merging pattern-based architectural methodology with storytelling and ecological awareness, this thesis reimagines public markets as active learning environments and living systems that are functional, felt, understood and remembered through architecture.
Keywords: Fish market, pattern language , Gothenburg , local food system, fiskhamnen